Cellular density‐dependent increases in HIF‐1α compete with c‐Myc to down‐regulate human EP4 receptor promoter activity through Sp‐1‐binding region. Issue 6 (11th November 2018) - Seira, Naofumi; Yamagata, Kazuyuki; Fukushima, Keijo; Araki, Yumi; Kurata, Naoki; Yanagisawa, Naoki; Mashimo, Masato; Nakamura, Hiroyuki; Regan, John W.; Murayama, Toshihiko; Fujino, Hiromichi
Abstract: The up‐regulated expression of E‐type prostanoid (EP) 4 receptors has been implicated in carcinogenesis; however, the expression of EP4 receptors has also been reported to be weaker in tumor tissues than in normal tissues. Indeed, EP4 receptors have been suggested to play a role in the maintenance of colorectal homeostasis. This study aimed to examine the underlying mechanisms/reasons for why inconsistent findings have been reported regarding EP4 receptor expression levels in homeostasis and carcinogenesis by focusing on cellular densities. Thus, the human colon cancer HCA‐7 cells, which retain some functional features of normal epithelia, and luciferase reporter genes containing wild‐type or mutated EP4 receptor promoters were used for elucidating the cellular density‐dependent mechanisms about the regulation of EP4 receptor expression. In silico analysis was also utilized for confirming the relevance of the findings with respect to colon cancer development. We here demonstrated that the expression of EP4 receptors was up‐regulated by c‐Myc by binding to Sp‐1 under low cellular density conditions, but was down‐regulated under high cellular density conditions via the increase in the expression levels of HIF‐1α protein, which may pull out c‐Myc and Sp‐1 from DNA‐binding. The tightly regulated EP4 receptor expression mechanism may be a critical system for maintaining homeostasis in normal colorectal epithelial cells. Therefore, once the system is altered, possibly due to the transient overexpression of EP4 receptors, it may result in aberrant cellular proliferation and transformation to cancerous phenotypes. However, at the point, EP4 receptors themselves and their mediated homeostasis would be no longer required.